Analisis Sastra Siber Puisi “Pada Suatu Hari Nanti” Karya Sapardi Djoko Damono Dengan Pendekatan Ekspresif Pada Website Narakata.Id - Amalia Divani Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article discusses the poem “Pada Sebuah Hari Nanti” by Sapardi Djoko Damono through an expressive approach in the context of cyber literature. The expressive approach is used to interpret the poem as a reflection of the poet’s feelings, thoughts, and life experiences. Analysis is carried out on the verses of the poem to reveal how Sapardi expresses awareness of the transience of life, deep love, and the desire to remain present through literary works. This study uses a descriptive qualitative method with library study techniques and data recording. The findings show that this poem is not only a medium for Sapardi’s personal expression, but also a means for the eternity of meaning in digital space. The Narakata.id platform as a publication media also expands the reach of literary appreciation, making this poem part of the transformation of literary works into a more inclusive and interactive digital form.